Renormalization-group study of the superconducting-to-pseudogap transition - Springer, Daniel (2014)
The amount of hole- or electron-doping of a high-temperature superconductor determines the low-temperature long-range order. With increased doping the long-range order changes from a Mott insulating to a high-temperature superconducting phase. In between these two regimes a rather intriguing phase with a pre-formed energy gap but no superconductivity is observed.